Elucidation of host diversity of the VanD-carrying genomic islands in enterococci and anaerobes. Issue 1 (4th January 2022) - Hashimoto, Yusuke; Hisatsune, Junzo; Suzuki, Masato; Kurushima, Jun; Nomura, Takahiro; Hirakawa, Hidetada; Kojima, Naoko; Ono, Yuichi; Hasegawa, Yutaka; Tanimoto, Koichi; Sugai, Motoyuki; Tomita, Haruyoshi
Abstract: Background: VanD is a rare type of vancomycin resistance worldwide. However, the host diversity of the vanD gene cluster and the structural similarity of their genomic islands are not well understood. Methods: Three VanD-type Enterococcus faecium strains (AA620, AA622 and AA624) isolated from a Japanese patient who underwent vancomycin treatment in 2017 were analysed. This study utilized WGS analysis to characterize the three VanD-type E. faecium strains and describes the diversity of hosts possessing VanD-carrying genomic islands. Results: The three isolates exhibited variable MICs of vancomycin. In the relatively vancomycin-resistant AA620, mutations were identified in vanSD and ddl . The strains AA622 and AA624 had intact ddl and harboured two vanD gene clusters. qRT-PCR results revealed the ddl mutation to be a factor affecting the high vancomycin resistance range of AA620. WGS data showed the 155 kb and 185 kb genomic islands harbouring the vanD gene cluster inserted in the coding region of the lysS gene, located in the chromosome in AA620 and AA622/624, respectively. Comparing the VanD-carrying genomic islands to available sequences of other enterococci and enteric anaerobes revealed how the genomic islands of these organisms isolated worldwide shared similar core genes and backbones. These anaerobes belonged to various genera within the order Eubacteriales. The phylogenetic cluster of the genomic island core genome alignment did not correlate with the host-species lineage, indicating horizontal gene transfer in the gut microbiota. Conclusions: By horizontal gene transfer, various bacteria forming the gut microbiota maintain VanD-carrying genomic islands.